2019
DOI: 10.7759/cureus.4677
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Echo-planar Diffusion-weighted Imaging in the Diagnosis of Intra-cerebral Abscess by Taking Histopathological Findings as the Gold Standard

Abstract: Objective To determine the diagnostic accuracy of echo-planar diffusion-weighted imaging (DWI) in the diagnosis of intra-cerebral abscesses by taking histopathological findings as the gold standard. Subject and methods A retrospective cross-sectional study was performed from July 2014 to June 2015 at a tertiary care hospital in Karachi. A total of 462 patients, who were referred for magnetic resonance imaging (MRI) brain, presenting with clinical suspicion of an intra-cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Some studies have reported that the duration of antibiotic therapy is determined with the help of MRI and DWI results [23]. It has been suggested that, along with the antibiotic regimen, MRI and DWI are helpful tools in the diagnosis of brain abscesses [1,24,25]. In the present study, MRI and DWI were used to diagnosis the brain abscess.…”
Section: Discussionmentioning
confidence: 83%
“…Some studies have reported that the duration of antibiotic therapy is determined with the help of MRI and DWI results [23]. It has been suggested that, along with the antibiotic regimen, MRI and DWI are helpful tools in the diagnosis of brain abscesses [1,24,25]. In the present study, MRI and DWI were used to diagnosis the brain abscess.…”
Section: Discussionmentioning
confidence: 83%
“…At present, DWI is the only non-invasive method for measuring the motion of the water molecules in living tissue. By measuring the ADC value, it can clarify the microscopic diffusion movement of water molecules inside and outside living tissues, and then understand the quantitative movement of water molecules ( 7 ). Choi et al ( 8 ) reported that there is a close relationship between the ADC value and cell structure.…”
Section: Discussionmentioning
confidence: 99%
“…1. Indeed, DWI is a valuable tool for diagnosing brain abscesses with high sensitivity and specificity [20]. The diffusion restriction in the central liquid portion of a pyogenic abscess is related to the viscosity of the pus and the presence of neutrophils.…”
Section: Neuroimagingmentioning
confidence: 99%